Nitric oxide‐releasing antibacterial albumin plastic for biomedical applications. Issue 6 (19th February 2018) - Jones, Alexander; Pant, Jitendra; Lee, Eliza; Goudie, Marcus J.; Gruzd, Alexey; Mansfield, Joel; Mandal, Abhyuday; Sharma, Suraj; Handa, Hitesh
Abstract: Designing innovative materials for biomedical applications is desired to prevent surface fouling and risk of associated infections arising in the surgical care patient. In the present study, albumin plastic was fabricated and nitric oxide (NO) donor, S ‐nitroso‐ N ‐acetylpenicillamine (SNAP), was incorporated through a solvent swelling process. The albumin‐SNAP plastic was evaluated in terms of mechanical and thermal properties, and bacterial adhesion to the plastic surface. Thermal and viscoelastic analyses showed no significant difference between albumin‐SNAP plastics and pure, water‐plasticized albumin samples. Bacteria adhesion tests revealed that albumin‐SNAP plastic can significantly reduce the surface‐bound viable gram‐positive Staphylococcus aureus and gram‐negative Pseudomonas aeruginosa bacterial cells by 98.7 and 98.5%, respectively, when compared with the traditional polyvinyl chloride medical grade tubing material. The results from this study demonstrate NO‐releasing albumin plastic's potential as a material for biomedical device applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1535–1542, 2018.